Why Should Clinicians Publish? - Choorakuttil, Rijo Mathew (Journal of Gastrointestinal and Abdominal Radiology, 2018)
Often, in personal conversations, we hear several reasons including time, resources, and usefulness of published reports and of research itself for the lack of interest by clinicians to publish scientific manuscripts. The number of patients treated is considered a more useful indicator of clinical care acumen than the number of scientific manuscripts published. I argue that publishing a scientific manuscript that results from a research study is an integral part of clinical medicine and that lack of publishing renders clinical care incomplete.
Keywords: Keywords; research; manuscript; publishing